A estratégia de sustentabilidade como fator de geração de valor para a empresa: o caso do ABN AMRO Real, no Brasil, de 2002 a 2008 - Costa, Luciana Aparecida da (2008)
This dissertation is an exploratory case study about Banco Real strategy and its focus on sustainability, in Brazil, since 2002. It aims to define sustainable development and presents different views of a variety of authors about this issue. It has been concluded a research with some clients and employees of Banco Real. Some secondary data, during the period of the case study, has been found inside the bank. Finally, through the analysis of the research and the data, it has been concluded that Banco Real has adopted the strategy of sustainability, since 2002, and there are some factors which shows, without a precise conclusion, that this strategy creates some value to the bank.